Имитационное моделирование распределения времени нарастания импульса тока - Петков, Александр Александрович (НТУ "ХПИ", 2016)
Установлено, что верхняя оценка вероятности безотказной работы генератора импульсов тока (по параметру время нарастания) соответствует варианту нормального распределения эквивалентных параметров разрядной цепи, а нижняя оценка - распределению эквивалентных параметров разрядной цепи по равномерному закону. Получены зависимости, позволяющие определять значения вероятности безотказной работы во всем диапазоне изменения параметров элементов разрядной цепи для варианта их относительных отклонений от номинальных значений равных 10%. Материалы, представленные в работе, могут быть использованы для исследования надежности функционирования генераторов импульсов тока.

Study the impact of the discharge circuit parameters on the distribution of values of the rise time of the pulse current and the probability of failure of the current pulse generator. Simulation modeling of the distribution of values of the rise time of the current pulse. The paper shows the expression that shows the approximate dependence of the rise time of the pulse current for the entire range of variation of the values of the parameters of the circuit elements of the discharge. The error of approximation does not exceed 1%. The influence of the parameters of the discharge circuit in the form of the distribution of values of the rise time of the current pulse. The dependencies to determine the probability of failure-free operation throughout the range of parameters of the discharge circuit elements. The paper investigated the relationship of deviations of parameters of the discharge circuit, the deviation of the current pulse rise time and the probability of failure-free operation of the generator of current pulses. The results allow to predict the reliability of the current pulse generator.
Simulation of the distribution of the current pulse rise time
Keywords: генератор; импульсы тока; закон распределения; вероятность безотказной работы; разрядная цепь; имитационное моделирование